Exposure–Response Relationship of T‐DM1: Insight Into Dose Optimization for Patients With HER2‐Positive Metastatic Breast Cancer. Issue 5 (31st January 2014) - Wang, J; Song, P; Schrieber, S; Liu, Q; Xu, Q; Blumenthal, G; Amiri Kordestani, L; Cortazar, P; Ibrahim, A; Justice, R; Wang, Y; Tang, S; et al.
<x xml:space="preserve">Abstract</x> Exposure–response (E–R) analyses for ado‐trastuzumab emtansine (T‐DM1, Kadcyla) were performed using data from a randomized, active control (lapatinib plus capecitabine) trial in patients with human epidermal growth factor 2–positive metastatic breast cancer. Kaplan–Meier survival analyses stratified by T‐DM1 trough concentration on day 21 of cycle 1 (Cmin, C1D21) were performed for overall survival (OS) and progression‐free survival (PFS). E–R analyses indicated that after adjusting for baseline risk factors, higher T‐DM1 exposure is associated with improved efficacy. T‐DM1–treated patients with Cmin, C1D21 lower than the median value had values of OS and PFS comparable to those of the active control arm. The percentage of patients who received T‐DM1 dose adjustments was similar across the exposure range and was lower than that of the active control arm. Our findings suggest that there may be an opportunity to optimize Kadcyla dose in the patient subgroup with low T‐DM1 exposure for improved efficacy with acceptable tolerability. Clinical Pharmacology & Therapeutics (2014); 95 5, 558–564. doi:10.1038/clpt.2014.24